Memaknai Communio dalam Umat Kristen Berdasarkan Efesus 4:5 - Jindung, Pilipus Benizi; Firman, Karifansius; Sandri, Yohanes Arnoldus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The development of information and communication technology (ICT) has had a significant impact on religious life, including the fellowship of Christians. ICT offers opportunities to expand the reach of ministry, strengthen connections between congregations, and facilitate Bible learning. However, potential dangers also exist; ICT can erode the values of communion and fuel individualism, contrary to the teachings of Christ. Ephesians 4:5 (